Adhesion tunable bio-inspired dry adhesives by twisting - Kang, Oh Hyun; Lee, Sung Ho; Yun, Jung Hwan; Yi, Hak; Kwak, Moon Kyu; Lee, Sang Ryong (International journal of precision engineering and manufacturing, 2017)
We report on a control method by twisting the adhesion property of a bio-inspired dry adhesive with mushroom-shaped micro structures. The fabricated artificial dry adhesive has a strong adhesive force in all directions; however, this adhesive is considerably strong to detach simply for reversible usages. This study proposes twisting a mushroom-shaped artificial dry adhesive for easy a detachment method that makes a pull-off force decrease from 14 N/cm 2 to nearly 0. In addition, the optimal process parameters of the twisting detachment are studied by experimentally comparing the pull-off force, net torque, and required time depending on the thickness of the adhesive and angular velocity of twisting. Result indicates that thin adhesive (1.2 mm) and high angular velocity (0.0436 rad/s) provide a good detachment performance. For the feasible application of the proposed method, a glass transportation robot was used for demonstration and a glass substrate was transported several times .